Construction, characterization and properties investigation of polyaniline different nanostructures in acidic ionic liquids media based on imidazole and pyridine - Ehsan Nazarzadeh Zare; Moslem Mansour Lakouraj; Aref Ashna (شیمی کاربردی روز, 2018)
In this paper, polyaniline nanostructurs with different morphologies were synthesized in medium containing ionic liquids (ILs) such as, imidazolium buthyl sulfonate [IMBS], pyridinium chloro acetic acid [PyCAA][Cl] and pyridinium hydrogen sulfate [HPy][HSO4] with various weight ratios of aniline/ILs. Structure and properties of synthesized polyanilines were investigated by using FTIR spectroscopy, UV-Vis, XRD, SEM and TGA. Electrical conductivity and viscosity of synthesized polyanilines were studied by four probe technique and Ubbelohde viscometer, respectively. XRD patterns and SEM images showed that acidic ILs are affected in crystallinity and formation of one and many dimensional nanostructures. Electrical conductivity, solubility, viscosity and thermal stability of synthesized polyanilines in acidic ILs medium are more than that the synthesized polyaniline in standard condition. It seems, ILs as a soft template caused growth and order of polyaniline chains in various morphologies.